2017
DOI: 10.1111/pbi.12751
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing auxin accumulation in maize root tips improves root growth and dwarfs plant height

Abstract: SummaryMaize is a globally important food, feed crop and raw material for the food and energy industry. Plant architecture optimization plays important roles in maize yield improvement. PIN‐FORMED (PIN) proteins are important for regulating auxin spatiotemporal asymmetric distribution in multiple plant developmental processes. In this study, ZmPIN1a overexpression in maize increased the number of lateral roots and inhibited their elongation, forming a developed root system with longer seminal roots and denser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 50 publications
3
78
0
4
Order By: Relevance
“…Subsequently, they showed that rice PHT1.8 performs a novel biological function during crosstalk between Pi and auxin signalling. This was one of the recent reports that provided clues for the link between auxin and -Pi responses [99]. Sulphate transporters have also implicated in grain PA and P content regulation.…”
Section: Phosphate In Seedsmentioning
confidence: 81%
“…Subsequently, they showed that rice PHT1.8 performs a novel biological function during crosstalk between Pi and auxin signalling. This was one of the recent reports that provided clues for the link between auxin and -Pi responses [99]. Sulphate transporters have also implicated in grain PA and P content regulation.…”
Section: Phosphate In Seedsmentioning
confidence: 81%
“…This similitude seems to be the result of duplication events among the genes and a domain rearrangement due to alternative splicing 63,64 , which has modified the number of ARF genes in different species 53,62 . An expression analysis in silico of ZmARF27 showed that this gene in maize is mainly expressed in the seed, tassel and ear 59 , tissues affected by auxin concentration [65][66][67] . For instance, Chen et al 65 found that there is a positive correlation between IAA concentration and ear height.…”
Section: Discussionmentioning
confidence: 99%
“…Other research suggests yield benefits resulting from auxin accumulation in the roots, although the link with whole-plant hydraulics was not documented. On maize, Li et al . (2018) found that maize mutants over-expressing ZmPIN1a exhibited an increase in auxin export from the shoot to the root where its accumulation in the root tips drove enhanced root development that was associated with increased yields under drought, likely through improved water acquisition.…”
Section: Discussionmentioning
confidence: 99%